2007
DOI: 10.1097/gme.0b013e31802d979b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary equol on body weight gain, intra-abdominal fat accumulation, plasma lipids, and glucose tolerance in ovariectomized Sprague-Dawley rats

Abstract: In ovariectomized rats, dietary equol administration attenuates weight gain and shows favorable metabolic effects. However, because of its mild uterotrophic activity, its use in the prevention of postmenopausal weight gain and related metabolic disorders in women with an intact uterus is questionable in terms of safety and warrants further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
46
1
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 50 publications
12
46
1
5
Order By: Relevance
“…Whereas, 13-week treatment (post) with VA (50 and 100 mg/kg b.wt) considerably alleviated (p < 0.01) those excessive body weight gain which was observed in OVX rats owing to estrogenic activity. Several studies had shown that the substance or drug with estrogenic activity could significantly lower the ovariectomy-induced weight gain (Rachon et al, 2007 and. Also, the UI value was substantially lowered in OVX rats and thus proving that the surgical procedure (atrophy of uterus) was successful.…”
Section: Resultsmentioning
confidence: 97%
“…Whereas, 13-week treatment (post) with VA (50 and 100 mg/kg b.wt) considerably alleviated (p < 0.01) those excessive body weight gain which was observed in OVX rats owing to estrogenic activity. Several studies had shown that the substance or drug with estrogenic activity could significantly lower the ovariectomy-induced weight gain (Rachon et al, 2007 and. Also, the UI value was substantially lowered in OVX rats and thus proving that the surgical procedure (atrophy of uterus) was successful.…”
Section: Resultsmentioning
confidence: 97%
“…Rachon et al reported that a 400 mg/kg diet of dietary equol decreased food intake and body fat in OVX rats. 48) Wu et al reported that the preventive effects of isoflavones on fat accumulation in early postmenopausal women depend on an individual's capacity to produce equol.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, treatment of ovx rats with oestrogen or any substance with estrogenic potential (i.e. phytoestrogens) attenuates ovariectomy induced weight gain and visceral fat deposition (Rachoń et al, 2007a;Rachoń et al, 2007b). Consistently, aromatase deficient or oestrogen receptor alpha (ER ) knockout mice develop obesity and related metabolic abnormalities again suggesting that oestrogen deprivation may play a pivotal role in postmenopausal weight gain in women (Heine et al, 2000;Jones et al, 2006).…”
Section: Menopause Hormonal Changes and Obesitymentioning
confidence: 99%